Qualidade nutricional e aceitabilidade da geleia convencional e light de maná cubiu - Furlaneto, Karina Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this work was to develop a light jelly manna cubiu sweetened with sucralose, evaluate its composition and acceptability. In the fresh fruit and bleached pulp manna cubiu were held the following physico-chemical analysis (soluble solids, pH, Acidity, reducing sugar), quantification of instrumental color and chemistries (Phenolic Compounds and Antioxidant Activity Totals by DPPH method). The jellies were prepared with a concentration of 60:40 (pulp crystallized sugar) for conventional and 60:40 (pulp: Crystal + sucralose sugar) for light jellies. For gelation thereof occur, citrus pectin was used. The jelly was bottled in the hot glass containers with a capacity of 320g, pre-sterilized closed and inverted. After filling the jellies were cooled naturally and stored at room temperature. Jelly were asked the following analyzes: Physical and chemical (soluble solids, pH, Acidity, reducing sugar and total reducing sugar), quantification of instrumental color, biochemical (Phenolic Compounds and Antioxidant Activity Totals by DPPH method), and microbiological analysis sensory analysis for the storage period of 120 days. The Soluble Solids content increased during the storage time. The treatments showed that the addition of sweetener (formulations light) caused a small increase of the pH value when compared with the conventional jelly. During the storage period, there was a small increase in Titratable Acidity levels, especially in light formulations. The Phenolic Compounds Total fell significantly in the first fifteen days of storage for all treatments, as the antioxidants did not change significantly during storage. The results of the gel did not show any microbiological contamination until 120 days of storage, appearing in satisfactory sanitary conditions. The Jelly Light 2 (60% + 28% sucrose pulp + 12% sucralose), showed greater acceptance and according to the assessment of purchase ...

O objetivo deste trabalho foi desenvolver uma geleia light de maná cubiu adoçada com sucralose, avaliar sua composição e aceitabilidade. No fruto in natura e na polpa branqueada de maná cubiu foram realizadas as seguintes análises físico-químicas (Sólidos Solúveis, pH, Acidez Titulável, açúcar redutor), quantificação da cor instrumental e análises bioquímicas (Compostos Fenólicos Totais e Atividade Antioxidante pelo método DPPH). As geleias foram preparadas com uma concentração de 60:40 (polpa:açúcar cristal) para a convencional e 60:40 (polpa:açúcar cristal + sucralose) para as geleias light. Para que ocorresse a geleificação das mesmas, foi utilizada pectina cítrica. A geleia foi envasada à quente em embalagens de vidro com capacidade para 320g, previamente esterilizadas fechadas e invertidas. Após o envase as geleias foram resfriadas naturalmente e estocados à temperatura ambiente. Nas geleias foram feitas as seguintes análises: físico-químicas (Sólidos Solúveis, pH, Acidez Titulável, açúcar redutor e açúcar redutor total), quantificação da cor instrumental, análises bioquímicas (Compostos Fenólicos Totais e Atividade Antioxidante pelo método DPPH), análise microbiológica e análise sensorial, durante o período de armazenamento de 120 dias. Os teores de Sólidos Solúveis aumentaram durante o tempo de armazenamento. Os tratamentos que apresentaram adição de edulcorante (formulações light), ocasionou pequena elevação do valor do pH quando comparados com a geleia convencional. Durante o período de armazenamento houve pequena elevação nos teores de Acidez Titulável, principalmente nas formulações light. Os Compostos Fenólicos Totais apresentaram redução significativa nos primeiros quinze dias de armazenamento para todos os tratamentos, já o antioxidantes não sofreram alterações ...
Processing technological and energetic evaluation of maná cubiu jelly
Keywords: Avaliação sensorial; Frutas tropicais; Geleia; Polpa de frutas - Analise; Jam